Subtle racism in English language: A socio-semiotic analysis of black-prefixed English lexicons - Olagbaju, Oladotun Opeoluwa; Ogunyemi, Kehinde Olufemi (Englisia Journal, 2021)
The English language has become a global language and as such, it is expected to be devoid of racial discrimination and prejudice. The English language has both verbal and non-verbal systems of communication which often requires semantic and semiotic analyses for the purpose of generating meaning. Most English words with the prefix 'black' have meanings that are either connotative or derogative. Using Jakobson’s transmutation theory, the study establishes the relationship between colour, culture, and racial prejudice in English language black-prefixed lexicons. This is a subtle form of racism when such words are taught in schools. The design adopted for this research was a qualitative, and no variables were manipulated because it was a library research. The study examined the socio-semiotic elements of black-prefixed words in the English language to establish that there is subtle racism in English expressions used and taught in schools. It was concluded that instruction in the language should be revitalized to eradicate racism of any form, especially in the second language classroom.